Pest categorisation of Fusarium brachygibbosum - EFSA Panel on Plant Health (PLH) (Wiley, 2021)
Abstract The EFSA Plant Health Panel performed a pest categorisation of Fusarium brachygibbosum Padwick. F. brachygibbosum is a well‐characterised fungal plant pathogen with opportunistic behaviour, mostly isolated along with other fungal pathogens in symptomatic hosts. It has been reported from Africa, America, Asia and Oceania where it is has been associated with a wide range of symptoms on approximately 25 cultivated and non‐cultivated plant species. The pathogen has been reported in Italy in soil/marine sediments and in quinoa (Chenopodium quinoa) and durum wheat (Triticum turgidum subsp. durum) seeds. The pathogen is not included in the EU Commission Implementing Regulation 2019/2072. This pest categorisation focused on a selected range of host plant species on which F. brachygibbosum fulfilled Koch′s postulates and was formally identified by multilocus gene sequencing analysis. Host plants for planting, seed of host plants and soil and other substrates originating in infested third countries are main pathways for the entry of the pathogen into the EU. There are no reports of interceptions of F. brachygibbosum in the EU. Host availability and climate suitability factors occurring in the EU are favourable for the establishment of the pathogen in Member States (MSs). Phytosanitary measures are available to prevent the introduction of the pathogen into the EU. Additional measures are available to mitigate the risk of entry and spread of the pathogen in the EU. Despite the low aggressiveness observed in some reported hosts, it has been shown that, in the areas of its present distribution, the pathogen has a direct impact on certain hosts (e.g. almond, onion, soybean, tobacco) that are also relevant for the EU. The Panel concludes that F. brachygibbosum satisfies all the criteria to be regarded as a potential Union quarantine pest. However, high uncertainty remains regarding the distribution of the pathogen in the EU and some uncertainty exists about its potential impact in the EU. Specific surveys and re‐evaluation of Fusarium isolates in culture collections could reduce these uncertainties.